Correlation between self-regulatory fatigue and physical activity in lung cancer patients undergoing comprehensive treatment - Qiaoling Li; Jing Zhang; Shasha Meng; Fengxiang Tian; Qinqin Mei; Hui Wang; Hong Qi (PLoS ONE, 2026)
Background Self-regulated fatigue is often assessed in studies of chronic diseases. Research is needed on the self-regulation of fatigue and physical activity in lung cancer patients undergoing treatment, and the impact of these factors on this population. Objective The goal of this study is to investigate the current status, influencing factors, and correlation between self-regulatory fatigue and physical activity in lung cancer patients undergoing comprehensive treatment. Methods We used a convenience sampling method to enroll 188 lung cancer patients admitted to two tertiary hospitals in Chengdu from October 2024 to April 2025. Data were collected using a general information questionnaire and two scales: the Self-Regulatory Fatigue Scale (SRF-S) and The International Physical Activity Questionnaire-long form (IPAQ-L). Results The mean self-regulatory fatigue score was 42.19 ± 9.06. The total metabolic equivalent (MET) of physical activity was 544.00 (0.00, 1386.00) MET-min/week, with leisure-time activity accounting for 429.00 (0.00, 1188.00) MET-min/week (data presented as median and interquartile range). Significant negative correlations were observed between Self-Regulatory Fatigue total scores and energy expenditure from housework, leisure activities, as well as total physical activity expenditure. Furthermore, self-regulatory fatigue was negatively correlated with both moderate-intensity and low-intensity physical activity, but positively correlated with high-intensity physical activity ( P < 0.05). Multiple linear regression analysis identified gender, physical activity intensity, and pre-diagnosis exercise habits as significant independent influencing factors of self-regulatory fatigue in these patients ( P < 0.05), collectively explaining 30.6% of the total variance ( R² = 0.306). Conclusion Engaging in appropriate leisure and household activities at moderate-to-low intensity may help alleviate the severity of self-regulatory fatigue in lung cancer patients undergoing comprehensive treatment. Healthcare providers should encourage appropriate activity to reduce the psychological burden and conserve self-regulatory resources.